KẾT QUẢ PHÂN TÍCH BÀO TỬ, PHẤN HOA TRONG HAI LỖ KHOAN VÙNG HÀ NỘI VÀ MỐI LIÊN HỆ VỚI BIẾN ĐỔI KHÍ HẬU VÀ HỆ THỰC VẬT TRONG HOLOCENE - Dương, Nguyễn Thị Thùy; Linh, Dương Mạnh (Vietnam Journal of Earth Sciences, 2011)
Characteristics of pollen and spore in sediment of the Hanoi area in relation to climate and vegetation change in HoloceneA palynological study of two sediment cores from the Hanoi area shows the climate change and human impact in Early and Middle Holocene. The abundance of tropical and subtropical vegetation in the period 10.5 to 5.8 Kcal. years BP shows humid and hot climate in the Hanoi area. However, there is a short time of cold and dry climate between 8.2 - 8.4 Kcal. years BP. After 6.5 Kcal.years ago, the diversity and abundance of tropical and subtropical vegetation shows a high rainfall and hot climate. The starting of human activities to be identifed in this area at about 6000 years ago, imprinted by the high values of Graminae and Alnus in both 2 cores.